Perceptions of teachers from a field school about the use of Active Methodologies: a case (Research, Society and Development, 2022)
In view of the advancement of science, technology and society, education follows a series of changes and, with this, it is necessary to increase pedagogical practices that structure teaching methodologies, however, as teaching evolves, the learning construction also changes. This study aimed to reflect on the perception of Basic Education teachers in a field school regarding Active Methodologies. The study is of a qualitative nature, of the case study type, its structure acquires a systematic and reflexive character, since the 'case' is inserted in a contemporary phenomenon, evaluated in a certain context. The results infer that teachers know the didactic-pedagogical foundations of Active Methodologies, as well as use such methods to mediate their classes in Basic Education, culminating in excellent yields in the construction of student learning. Teachers associate Active Methodologies as a target for meaningful learning, and in their discourses there is a locus rich in potentialities developed by the method, such as: autonomy, engagement, participation, collaboration and teamwork. The conclusions resume the importance of the method for the teaching and learning processes and reinforce the need to propagate continuing education for the use of Active Methodologies in Basic Education.